2021
DOI: 10.1161/jaha.120.015868
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Inhibition of Estrogen Regulation of the Serotonin Receptor 2B in Cardiomyocytes Exacerbates Cell Death in Hypoxia/Reoxygenation Injury

Abstract: Background Stress has emerged as an important risk factor for heart disease in women. Stress levels have been shown to correlate with delayed recovery and increased mortality after a myocardial infarction. Therefore, we sought to investigate if the observed sex‐specific effects of stress in myocardial infarction may be partly attributed to genomic interactions between the female sex hormones, estrogen (E2), and the primary stress hormones glucocorticoids. Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Another investigation of middle-aged women from the general population indicated that sexual assault was associated with a three to four-fold greater odds of a high carotid plaque score and the progression of carotid atherosclerosis over 5 years, although there were no associations with carotid intima-media thickness [44]. Most recently, a study suggested that traumatic stress might change the genomic interactions between glucocorticoid receptors and estrogen receptors, and thereby inhibit the cardioprotection that women typically experience from the hormone estrogen [45]. Although a paucity of data concerns the physiological effects of MST or other types of sexual violence in men, we can begin to theorize about these pathways based on literature concerning trauma, PTSD and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…Another investigation of middle-aged women from the general population indicated that sexual assault was associated with a three to four-fold greater odds of a high carotid plaque score and the progression of carotid atherosclerosis over 5 years, although there were no associations with carotid intima-media thickness [44]. Most recently, a study suggested that traumatic stress might change the genomic interactions between glucocorticoid receptors and estrogen receptors, and thereby inhibit the cardioprotection that women typically experience from the hormone estrogen [45]. Although a paucity of data concerns the physiological effects of MST or other types of sexual violence in men, we can begin to theorize about these pathways based on literature concerning trauma, PTSD and cardiovascular risk.…”
Section: Discussionmentioning
confidence: 99%
“…This cardiomyocyte protection is abolished by glucocorticoids, the main stress hormones, and therefore important in the context of women exposed to stress suffering from a heart attack. 129 Under physiological conditions, regulation of blood pressure occurs via 5-HT2AR signaling, whose activation induces vasoconstriction. 56 However, in a deoxycorticosterone acetate (DOCA)-salt-hypertensive rat model, which resembles human volume-overload induced chronic hypertension, contractions insensitive to the 5-HT2AR antagonist ketanserin were detected, together with increased 5-HT2BR expression.…”
Section: ■ 5-ht2rmentioning
confidence: 99%
“…Receptor activation or overexpression was further shown to lead to adverse remodeling with more collagen formation and reduced cardiac functions, while treatment with antagonists terguride and SB204741 reduced collagen deposition and fibrosis. , Interestingly, the important female sex hormone estrogen can prevent cardiomyocyte death by binding to an estrogen responsive element, which regulates 5-HT2BR transcription. This cardiomyocyte protection is abolished by glucocorticoids, the main stress hormones, and therefore important in the context of women exposed to stress suffering from a heart attack …”
Section: -Ht2rmentioning
confidence: 99%
“…By modulating the expression of the 5-HT receptor— 5-HT2BR— estrogens decrease cardiomyocyte death that occurs in response to hypoxia/re-oxygenation injury. Glucocorticoids, on the other hand, prevent 5-HT–mediated estrogen cardioprotection, exacerbating the size of the infarct areas in myocardial infarction ( Dhaibar et al, 2021 ). 5-HT protection by estrogens, being cancelled by glucocorticoids, evidence the deleterious effects that stress may have on women’s well-being, particularly under hypoxic conditions.…”
Section: Special Topicsmentioning
confidence: 99%